Astrocyte–Neuron Networks: A Multilane Highway of Signaling for Homeostatic Brain Function - Mederos, Sara; González-Arias, Candela; Perea, Gertrudis (Frontiers in Synaptic Neuroscience, 2018)
Research on glial cells over the past 30 years has confirmed the critical role of astrocytes in pathophysiological brain states. However, most of our knowledge about astrocyte physiology and of the interactions between astrocytes and neurons is based on the premises that astrocytes constitute a homogeneous cell type, without considering the particular properties of the circuits or brain nuclei in which the astrocytes are located. Therefore, we argue that more-sophisticated experiments are required to elucidate the specific features of astrocytes in different brain regions, and even within different layers of a particular circuit. Thus, in addition to considering the diverse mechanisms used by astrocytes to communicate with neurons and synaptic partners, it is necessary to take into account the cellular heterogeneity that likely contributes to the outcomes of astrocyte–neuron signaling. In this review, we briefly summarize the current data regarding the anatomical, molecular, and functional properties of astrocyte–neuron communication, as well as the heterogeneity within this communication.